Elaboration of Pelaruga Ecotourism on Economic Empowerment of the Community of Rumah Galuh Village, Langkat Regency - Theresia Bela Mutiara Uli Sagala; Uswatun Hasanah; Suhendi Suhendi (Universitas Dehasen Bengkulu, 2026)
The development of Pelaruga ecotourism in Rumah Galuh Village, Langkat Regency, has great potential to improve the welfare of the community. This study examines the impact of Pelaruga Ecotourism on the Economic Empowerment of the Community in Rumah Galuh Village, Langkat Regency, with independent variables including Infrastructure, Accommodation, Visitors, Local Tourism Businesses, and Promotion, and dependent variables such as Community Participation and Community Empowerment. Data was obtained through questionnaires distributed to the community and local tourism businesses using data analysis techniques in the form of Structural Equation Modeling (SEM) based on Partial Least Squares (PLS), also known as SEM-PLS, through Smart PLS 4 management. A sample of 133 respondents was taken from the population living in Rumah Galuh Village and around the Pelaruga Ecotourism Area. The analysis of this study shows that the outer model value of the validity and reliability test has been measured as valid in the relationship between latent variables and manifest indicators. Then, the inner model value in the hypothesis testing states the relationship between variables that are relative to the variable assessor that has an effect on the related variables.